User Interface and User Experience Design in Digital Learning Applications for Autistic Users with the Human-Centered Design Method - Nurdin, Muhammad Iman; Ashar, Muhammad; Akbar, Muhammad Iqbal; Lesmana, I Putu Dody (Universitas Negeri Malang, 2022)
Currently in Indonesia there are millions of school-age children. Some of them still have difficulty in accessing education, including children with special needs. Children with special needs are part of a society that is classified as vulnerable. Some institutions state that they are 10 times more likely to be out of school. Even when they go to school, the learning they receive tends to be not optimal, especially for autistic children. Autism is a disorder of overall human development that results in barriers to socialization, communication, and behavior. With the various obstacles they have, the learning process they receive tends to be less than optimal if it is not balanced with adequate facilities and infrastructure. Therefore, in this study, researchers want to design a digital learning application for autistic users based on a website, where the User Interface (UI) and User Experience (UX) of the learning application are tailored to the user's needs. By using the Human-Centered Design (HCD) method that focuses on humans in its manufacture. With these grounds and reasons, it is hoped that this research can produce a UI UX with a good level of usability, effectiveness, and user satisfaction.